Pendidikan Berbasis Masyarakat dalam Pendidikan Islam - Moh Masduki Moh Masduki (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
This paper intends to discuss several issues related to community-based education in the view of Islamic education. There are two objects of study that are addressed in this discussion. First, the importance of community-based education in the present context. Second, discussing community-based education in the perspective of Islamic studies. This paper is a literature study where the author will discuss these two objects by digging data from written sources. From this discussion the following results are obtained: community-based education which is also called in several terms (adult education, non formal education, community base education) is still relevant to be implemented at this time. This is caused by several things: the lack of capacity of the community in developing countries to access formal education, formal education is felt not to solve the interests of society, the incessant issue of democratization in all fields, and the principle of lifelong education. Based on these things, community-based education is relevant to be developed to date. In the Islamic perspective the community has a responsibility also to educate and nurture members of its community, this is stated in several verses of the Qur'an which explain that humans are created as beings better than other creatures to always invite goodness and prohibit munkar. This explanation is contained in the letter Ali Imran verses 110 and 104. Historical facts also show that at the time of the Prophet Muhammad's Islamic education began with the community such as: friend's house, mosque, suffah, al-badiah. In the current context of community education institutions in the form of majlis ta'lim, mosques, madrasa diniyah, skills courses all of which need to be revitalized as community-based education is still needed today.